"Beyond Emotion: Love as an Encounter of Myth and Drive" by Lubomir Lamy. (April 2016) - Marazziti, Donatella
The author comments on and criticizes some conclusions of the article by Lubomir Lamy entitled "Beyond Emotion: Love as an Encounter of Myth and Drive." In addition, she shows evidence that love may be considered an integrated neurobiobehavioral process and, as such, regulated by neural systems and circuits that underlie its emotional, cognitive, and behavioral expressions.